2007
DOI: 10.3168/jds.2006-565
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 and Ochratoxin A in Raw Bulk Milk from French Dairy Herds

Abstract: Mycotoxins in milk are a public health concern and have to be regularly monitored. A survey on the presence of aflatoxin M1 (AFM1) and ochratoxin A (OTA) in raw bulk milk was conducted in 2003 in the northwest of France, the main French milk-producing basin. Randomly selected farms (n = 132) were characterized by a diet based on corn silage and containing a large proportion of on-farm produced cereals, feeding sources that are frequently contaminated by mycotoxins. Farms were surveyed twice in winter and in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(73 citation statements)
references
References 20 publications
7
62
1
3
Order By: Relevance
“…in small children who consume large quantities of milk. In a survey on raw bulk milk in the northwest of France, in 132 farms surveyed in winter and summer using diets based on maize silage and containing large portion of farm produced cereal grains, the overall incidence of milk contamination with OTA at farm level was low [152]. OTA was detected in three out of 264 samples at a low level of 0.005 to 0.008 ng/mL.…”
Section: Systemic Occurrence and Excretion Of Ota In Ruminantsmentioning
confidence: 99%
“…in small children who consume large quantities of milk. In a survey on raw bulk milk in the northwest of France, in 132 farms surveyed in winter and summer using diets based on maize silage and containing large portion of farm produced cereal grains, the overall incidence of milk contamination with OTA at farm level was low [152]. OTA was detected in three out of 264 samples at a low level of 0.005 to 0.008 ng/mL.…”
Section: Systemic Occurrence and Excretion Of Ota In Ruminantsmentioning
confidence: 99%
“…In the case of AFB 1 , its presence in the food of dairy cattle leads to the emergence of AFM 1 in milk and dairy products (Boudra et al, 2007;Veldman et al, 1992). Aflatoxin B1 (ug kg-1) The natural occurrence of AFB 1 in feeds for dairy cows has shown that, in many cases aflatoxin levels exceeded regulation limits.…”
Section: Aflatoxin In Silagementioning
confidence: 99%
“…Estas contaminan los cereales y forrajes, ya sea en el campo, al momento de la cosecha, en el almacenamiento o en el procesamiento de alimentos balanceados, cuando las condiciones son favorables para su desarrollo (Espindola, 2006;Boudra et al, 2007).…”
unclassified
“…Luego que un animal la ingiere, de 0.5 a 5% de la toxina ingerida es biotransformada a Aflatoxina M 1 en el hígado (González et al, 2004), la cual es un metabolito tan tóxico como el contaminante original, y es posteriormente excretado en la leche. La cantidad de Aflatoxina M 1 encontrada en la leche representa normalmente del 1 al 2% de la Aflatoxina B 1 ingerida, llegando a encontrarse hasta el 6% en vacas de alta producción (Boudra et al, 2007).…”
unclassified